Personal Independence:The Hunger Games Novel By Suzanne Collins (2008): An Individual Psychological Approach - Yusuf, Zulfikar, Dr. Phil. Dewi Candraningrum. M.Ed (2016)
This research is about how is personal independence of the major and minor characters reflected in The Hunger Games novel. The objective of this study is to analyze the novel based on the individual psychological approach. The type of this research is qualitative research. Type of data of the study is novel taken from two data sources: primary and secondary. The primary data source is The Hunger Games novel published in 2008. While the secondary data sources are other materials taken from books, author's biography, essay, comments, critics and internet related to the study. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the individual psychology analysis, the study shows that the problem is faced by the major character is herown psychology condition to decide the appropriate ways for his life. Collins tells that the problem of the major character causes the personal independence of her social life because of her personality and causes some effect to inferiority feeling, striving to superiority, creative self, style of life, social interest, and functional finalism of the main character. Keywords: The Hunger Games, personal independence, courage, kind, obstacles, psychological theory.